Demographic Distribution of Leprosy Cases in South Sumatra Province: An Analysis of Health Profile Data, 2019–2023 - Sri Wahyuni Ihsan; Suci Fauziah; Sitti Zahra Inayah; Santri; Scholastika Melshe Pabutung (Journal of Epidemiology and Health Science, 2025)
Background: Leprosy remains a public health concern in Indonesia despite the achievement of national elimination status. Fluctuations in case numbers indicate ongoing transmission, particularly in certain regions. Objectives: This study aimed to analyze the distribution of leprosy cases in South Sumatra Province based on demographic characteristics during the period 2019–2023. Methods: A quantitative descriptive study design was employed using secondary data obtained from the Provincial Health Profile of South Sumatra. The data included annual leprosy case numbers, classification by type of leprosy (paucibacillary and multibacillary), and demographic variables. Data were analyzed descriptively and presented narratively, supported by bar charts and graphical visualizations to illustrate temporal trends and distribution patterns. Results: To showed that the number of leprosy cases fluctuated over the five-year period, with the highest number reported in 2019, followed by a general decline in subsequent years. Both paucibacillary and multibacillary cases were identified each year, with multibacillary cases remaining predominant. The persistence of multibacillary cases and the presence of cases among younger age groups suggest that leprosy transmission has not been fully interrupted. Geographic disparities, limited access to health services, and socio-cultural factors were identified as potential contributors to the observed distribution patterns. Conclusion: although the prevalence of leprosy in South Sumatra has declined, active transmission persists. Strengthening early case detection, improving access to health services, and enhancing the capacity of health workers are essential to support sustained leprosy control and prevent disability. These findings provide evidence to inform regional policy and targeted intervention strategies.